2013
DOI: 10.1097/aog.0b013e318278f56a
|View full text |Cite
|
Sign up to set email alerts
|

Independent Relation of Maternal Prenatal Factors to Early Childhood Obesity in the Offspring

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 30 publications
3
68
1
Order By: Relevance
“…Increased total weight gain and excessive GWG according to Institute of Medicine criteria have been associated with increased risks of offspring obesity, independent of maternal prepregnancy BMI. 4,6,[25][26][27][28][29]31,36 Associations of increased total GWG with offspring blood pressure, lipid profile and inflammatory markers are less consistent and seem to be mainly driven by offspring adiposity. 4,26,28 Accordingly, we observed associations of total and excessive GWG with increased childhood adiposity levels and increased risk of childhood overweight.…”
Section: Interpretation Of Main Findingsmentioning
confidence: 92%
“…Increased total weight gain and excessive GWG according to Institute of Medicine criteria have been associated with increased risks of offspring obesity, independent of maternal prepregnancy BMI. 4,6,[25][26][27][28][29]31,36 Associations of increased total GWG with offspring blood pressure, lipid profile and inflammatory markers are less consistent and seem to be mainly driven by offspring adiposity. 4,26,28 Accordingly, we observed associations of total and excessive GWG with increased childhood adiposity levels and increased risk of childhood overweight.…”
Section: Interpretation Of Main Findingsmentioning
confidence: 92%
“…We categorized gestational weight gain as excessive versus inadequate or adequate, thinking excessive weight gain detrimental and deserving of a point in our index. Ehrenthal et al 46 showed that only inadequate gestational weight gain was significantly associated with a higher BMI z score at age 4 years after adjusting for prepregnancy BMI and other covariates, suggesting that inadequate gestational weight gain contributes to increased adiposity. However, descriptive statistics indicated that inadequate gainers in our cohort engaged more often in healthy behaviors and may have gained inadequately because of health consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…The DMBC includes all infants born between 2004 and 2007 at the delivery hospital and who received well-child care at a pediatric practice network between 2004 and 2011; totaling 4852 mother-infant dyads at the time of the initial linkage, as previously described [33]. This study was approved by the Christiana Care Health System Institutional Review Board.…”
Section: Study Samplementioning
confidence: 99%